A new type of Robust broadband GaN HEMT‐based high power high‐pass/low‐pass 22.5° phase shifter. Issue 2 (February 2014) - Hettak, Khelifa; Ross, Tyler N.; Cormier, Gabriel; Wight, Jim S.
ABSTRACT This article proposes a new type of GaN HEMT‐based high power phase shifter operating at X‐band. The design includes a 22.5° phase shift network and a high power SPDT switch. The design and resulting performance are discussed in detail and are confirmed by experimental and simulation results, which are in good agreement up to 20 GHz. The one bit phase shifter exhibits good phase performance, insertion loss, and return loss. The proposed phase shifter MMIC has been successfully demonstrated using a 0.5 μm gate GaN HEMT process. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:347–350, 2014